2015
DOI: 10.1007/s10482-015-0575-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesonia sediminis sp. nov., isolated from a sea cucumber culture pond

Abstract: A yellow-pigmented, Gram-stain negative and facultatively anaerobic bacterium, designated MF326T , was isolated from a sample of sediment collected from a sea cucumber culture pond in Rongcheng, China (122°14 0 34 00 E 36°54 0 36 00 N). Cells of strain MF326T were found to be catalase negative and oxidase positive. Optimal growth was found to occur at 30°C and pH 7.0-7.5 in the presence of 2.0-3.0 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain MF326 T is a member of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The respiratory quinone of strain K7 T was determined to be MK-6 (100%). This was consistent with the species of the genus Mesonia [16,[19][20][21][22][23][24][25]. Polar lipids were extracted using a chloroform/methanol system and analysed using one-and two-dimensional TLC, as described previously [46].…”
Section: (Lc101490)supporting
confidence: 62%
See 3 more Smart Citations
“…The respiratory quinone of strain K7 T was determined to be MK-6 (100%). This was consistent with the species of the genus Mesonia [16,[19][20][21][22][23][24][25]. Polar lipids were extracted using a chloroform/methanol system and analysed using one-and two-dimensional TLC, as described previously [46].…”
Section: (Lc101490)supporting
confidence: 62%
“…Considering the 16S rRNA gene similarity of lower than 94.4 % to those of the close genera, the isolate cannot Table 2. Differential characteristics of strain K7 T and some phylogenetically related genera Strains: 1, K7 T ; 2, Mesonia, data from eight species (Nedashkovskaya et al [19,23], Choi et al [21], Kolberg et al [22], Sung et al [16], Lee et al [20], Kang and Lee [24], Wang et al [25] and this study); 3, Salinimicrobium, data from eight species (Lim et al [52], Zhang et al [14], Lee et al [48], Nedashkovskaya et al [53], Subhash et al [54], Kim et al [55] and Chen et al [56]); 4, Salegentibacter, data from ten species (Nedashkovskaya et al [49,57,58], Siamphan and Kim [15], Xia et al [59], Ivanova et al [60], Yoon et al [61,62], McCammon and Bowman [63] and Liang et al [64]); 5, Zunongwangia data from four species (Shao et al [13], Fidalgo et al [65], Rameshkumar et al [50] and Qin et al [66]). 6, Leeuwenhoekiella, data from six species (Nedashkovskaya et al [47,67], Pinhassi et al [68], Liu et al [17], Si et al [69] and this study); Major quinone and major polar lipids of all species were MK-6 and phosphatidylethanolamine, respectively.…”
Section: (Lc101490)mentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a total of 8 species of Mesonia have been validly described (Nedashkovskaya et al, 2003, 2006; Kang and Lee, 2010; Lee et al, 2012; Choi et al, 2015; Kolberg et al, 2015; Wang et al, 2015; Sung et al, 2017). All species isolated from the ocean and some additional species can hydrolyze gelatin (Nedashkovskaya et al, 2003; Sung et al, 2017), casein (Nedashkovskaya et al, 2003; Choi et al, 2015; Sung et al, 2017), fucoidan (Urvantseva et al, 2006), Tween 80 (Nedashkovskaya et al, 2006; Kang and Lee, 2010; Choi et al, 2015; Wang et al, 2015). Earlier studies found that some strains of the genus can form biofilms (Jeong et al, 2016) and are multiresistant (Miranda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%